النظام القانوني لشركة تسيير بورصة القيم المنقولة في الجزائر - عبد الوهاب, صالحي; اسلام, عطيلي (جامعة الوادي - University eloued, 2022)
حاولت الدراسة إلقاء الضوء على أهم الهيئات أو الأجهزة المسؤولة عن تنظيم وسير عمليات بورصة القيم المنقولة، والمتمثلة في شركة تسيير بورصة القيم المنقولة (SGBV) ، لما لها من دور فعال تقوم به في السوق المالية، والتي نظمها المشرع الجزائري بموجب المرسوم التشريعي 93/10 المؤرخ في 23 ماي 1993، وخصها بنظام قانوني سواء من حيث تأسيسها أو تنظيمها أو المهام الموكولة لها، مما أدى بنا إلى دراستها من خلال التعرض لمفهومها والوقوف على أهم الخصائص التي تتمتع بها، والأجهزة الإدارية المكونة لها، وتكييفها القانوني، لاسيما أن المشرع اعتبرها شركة ذات أسهم تخضع في أغلب الأحيان إلى القواعد العامة المتعلقة بشركة المساهمة في القانون التجاري، إلا أننا خلصنا إلى أنها بالإضافة إلى تلك الأحكام فقد خصها المشرع ببعض الأحكام غير المألوفة في القانون التجاري سواء من حيث رأس مالها أو الشركاء المنتسبين لها، بالإضافة إلى خضوعها للرقابة الخارجية التي تمارسها عليها لجنة تسيير عمليات البورصة ومراقبتها، مما يجعلها شركة مهنية ذات طابع خاص غرضها مختلف عن الشركات الأخرى The study attempted to shed light on the most important bodies or agencies responsible for regulating and running the operations of the stock exchange, represented by the SGBV management company, because of its effective role in the financial market, which was organized by the Algerian legislator according to Legislative Decree 10/93 of On May 23, 1993, he singled out a legal system other than him in terms of its establishment, organization or tasks assigned to it, which led us to study it through exposure to its concept and to stand on the most important characteristics that Baha and the administrative organs that make up it, and its legal adaptation, especially since the legislator considered it a company with shares Most of the time they are subject to the general rules related to the joint stock company in the commercial law, but we concluded that in addition to these provisions, the legislator has singled out some unfamiliar provisions in the commercial law, whether in terms of its capital or its affiliated partners, in addition to its subjection to the external control that it exercises. It is regulated by the Stock Exchange Operations Steering and Monitoring Committee, which makes it a professional company of a special nature with different presentation from other companies
مذكرة ماستر
Keywords: شركة؛ البورصة؛ تسيير بورصة القيم المنقولة؛ الأسهم؛ السوق المالية، الوساطة; company; The stock exchange, the management of the stock exchange, the stock exchange, the stock market, Mediation.